Respuesta :
The solution of the equations y = –x² + x + 2 and y = –x + 3 will be (1, 2). Then the correct option is A.
What is the solution of the equation?
The solution of the equation means the value of the unknown or variable.
The equation is given below.
y = –x² + x + 2 ...1
y = –x + 3 ...2
From equation 1 and 2, we have
–x² + x + 2 = –x + 3
x² – 2x + 1 = 0
Then the factor of the above equation will be
x² – 2x + 1 = 0
x² – x – x + 1 = 0
(x – 1)(x – 1) = 0
x = 1
Then the value of y will be
y = -1 + 3
y = 2
The solution of the equations will be (1, 2).
Then the correct option is A.
More about the solution of the equation link is given below.
https://brainly.com/question/545403
#SPJ2